Respuesta :
[tex]\dfrac{\cos^2\O\cdot\tan^2\O}{1-\cos^2\O}=\dfrac{\cos^2\O\cdot\tan^2\O}{\sin^2\O}=\dfrac{\cos^2\O}{\sin^2\O}\cdot\tan^2\O\\\\=\dfrac{1}{\dfrac{\sin^2\O}{\cos^2\O}}\cdot\tan^2\O=\dfrac{1}{\left(\dfrac{\sin\O}{\cos\O}\right)^2}\cdot\tan^2\O=\dfrac{1}{\tan^2\O}\cdot\tan^2\O\\\\=\dfrac{\tan^2\O}{\tan^2\O}=1[/tex]
[tex]Used:\\\\\sin^2\O+\cos^2\O=1\to1-\cos^2\O=\sin^2\O\\\\\tan\O=\dfrac{\sin\O}{\cos\O}[/tex]
[tex]Used:\\\\\sin^2\O+\cos^2\O=1\to1-\cos^2\O=\sin^2\O\\\\\tan\O=\dfrac{\sin\O}{\cos\O}[/tex]